Assessment of safety and interferon gamma responses of Mycobacterium bovis BCG vaccine in goat kids and milking goats. Issue 7 (10th February 2016) - Pérez de Val, Bernat; Vidal, Enric; López-Soria, Sergio; Marco, Alberto; Cervera, Zoraida; Martín, Maite; Mercader, Irene; Singh, Mahavir; Raeber, Alex; Domingo, Mariano
Abstract: Vaccination of domestic animals has emerged as an alternative long-term strategy for the control of tuberculosis (TB). A trial under field conditions was conducted in a TB-free goat herd to assess the safety of the Mycobacterium bovis BCG vaccine. Eleven kids and 10 milking goats were vaccinated with BCG. Bacterial shedding and interferon gamma (IFN-γ) responses were monitored throughout the study. Comprehensive pathological examination and mycobacterial culture of target tissues were performed. BCG vaccine strain was only isolated from the draining lymph node of the injection site of a kid euthanized at week 8 post-vaccination. The remaining animals were euthanized at week 24. Six out of 20 showed small granulomas at the injection site. BCG shedding was not detected in either faeces or in milk throughout the study. All vaccinated kids showed BCG-induced IFN-γ responses at week 8 post-vaccination. BCG vaccination of goats showed no lack of biological safety for the animals, environment and public health, and local adverse reactions were negligible.